Saliva proteome profiling reveals potential salivary biomarkers for detection of oral cavity squamous cell carcinoma - Wu, Chih-Ching; Chu, Hao-Wei; Hsu, Chia-Wei; Chang, Kai-Ping; Liu, Hao-Ping (Proteomics (Weinheim), 2015)
Oral cavity squamous cell carcinoma (OSCC), which is frequently associated with poor prognosis and mortality, is a leading cause of cancer‐related death worldwide. Discovery of body fluid accessible biomarkers is needed to improve OSCC screening. To this end, we profiled proteomes of saliva from the healthy volunteers, the individuals with oral potentially malignant disorders (OPMD), and the OSCC patients by means of SDS‐PAGE coupled with LC‐MS/MS. In the control, the OPMD, and the OSCC groups, 958, 845, and 1030 salivary proteins were detected, respectively. With spectral counting‐based label‐free quantification, 22 overexpressed salivary proteins were identified in the OSCC group compared with the healthy controls and the OPMD individuals. Among them, resistin (RETN) was subjected to further validation with an independent cohort using ELISA. The data confirmed that the salivary RETN levels in the OSCC patients were significantly higher than that in the healthy or in the OPMD group. Moreover, the elevated levels of salivary RETN were highly correlated with late‐stage primary tumors, advanced overall stage, and lymph‐node metastasis. Our results not only reveal that profiling of saliva proteome is feasible for discovery of OSCC biomarkers, but also identify RETN as a potential salivary biomarker for OSCC detection.